Pharmacokinetic study of prolonged release capsules of mebeverine - A. L. Khokhlov; Yu. A. Dzhurko; L. N. Shitov; I. I. Yaichkov; A. M. Shitova; L. A. Khozova; A. E. Miroshnikov (LLC "Publisher OKI", 2017)
Pharmacokinetic study of prolonged release capsules of mebeverine was carried out on 24 volunteers. It is known that the drug substance is completely metabolized due to first-pass effect. Therefore, pharmacokinetic parameters of the main metabolites -mebeverine acid and desmethyl mebeverine acid were measured. Bioanalytical method was developed to measurement of concentrations of these metabolites in blood plasma by using HPLC-MS/MS.